The Occupation of Migration in Uzbekistan - Baxriddinov K.B. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This article analyzes the causes of migration in Uzbekistan. The author discussed the work done to regulate external migration and support migrants